Luminescent lanthanide coordination compounds as potential mitochondria-targeting probes: Molecular engineering to bioimaging. (September 2022) - Reddy, M.L.P.; Bejoymohandas, K.S.; Divya, V.
Abstract: Mitochondria are vital organelles in eukaryotic cells, and can perform critical roles in supplying energy and maintaining cell functions. As a consequence, the design of mitochondria-targeting luminescent probes and the realisation of real-time mitochondrial activity acquisition are valuable tools in the study and therapy of mitochondrial dysfunction in diseases. Recently, lanthanide molecular compounds have emerged as potential mitochondria-targeting probes due to their low photobleaching propensity, sharp emission lines, and long excited-state lifetimes, which allow for time-resolved detection for increased sensitivity. A wide range of mitochondria-targeting luminescent lanthanide probes have been developed and employed for the detection of various reactive oxygen and bioactive species at the subcellular level in recent years, and the current review summarises all these advances. The design strategies, sensing mechanisms, and applications in bio-imaging of various reactive oxygen species in mitochondria are detailed here. Highlights: Mitochondria are energy-producing organelles that play an important role in cell life. Understanding of mitochondria-specific imaging can help us to design robust organelle-targeting therapeutic reagents. Due to their unique photophysical properties, lanthanide complexes are considered ideal probes for bioimaging. An overview of lanthanide complexes that target mitochondria is highlighted in this article. The design concepts, sensing mechanisms and applications in bioimaging are detailed here.